2007
DOI: 10.1073/pnas.0611487104
|View full text |Cite
|
Sign up to set email alerts
|

The Fas pathway is involved in pancreatic β cell secretory function

Abstract: Pancreatic ␤ cell mass and function increase in conditions of enhanced insulin demand such as obesity. Failure to adapt leads to diabetes. The molecular mechanisms controlling this adaptive process are unclear. Fas is a death receptor involved in ␤ cell apoptosis or proliferation, depending on the activity of the caspase-8 inhibitor FLIP. Here we show that the Fas pathway also regulates ␤ cell secretory function. We observed impaired glucose tolerance in Fas-deficient mice due to a delayed and decreased insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 46 publications
1
57
2
Order By: Relevance
“…Human islets were cultured in CMRL-1066 medium containing 5.5 mmol/l glucose and 100 units/ml penicillin, 100 g/ml streptomycin, and 10% FCS (Invitrogen, Carlsbad, CA). Mouse islets were isolated using Collagenase type 4 (Worthington, Lakewood, NJ) as described previously (17) and cultured in RPMI 1640 containing 11.1 mmol/l glucose. In culture, a glucose concentration of 11.1 mmol/l accomplishes the lowest frequency of ␤-cell apoptosis in mouse islets (18 -20).…”
Section: Methodsmentioning
confidence: 99%
“…Human islets were cultured in CMRL-1066 medium containing 5.5 mmol/l glucose and 100 units/ml penicillin, 100 g/ml streptomycin, and 10% FCS (Invitrogen, Carlsbad, CA). Mouse islets were isolated using Collagenase type 4 (Worthington, Lakewood, NJ) as described previously (17) and cultured in RPMI 1640 containing 11.1 mmol/l glucose. In culture, a glucose concentration of 11.1 mmol/l accomplishes the lowest frequency of ␤-cell apoptosis in mouse islets (18 -20).…”
Section: Methodsmentioning
confidence: 99%
“…This bimodal effect was shown to involve the Fas signalling pathway, which can switch from a mitogenic signal to induction of apoptosis when the FLICE-inhibitory protein (FLIP) is inactive (Maedler et al 2006). This pathway was also found to be important in sustaining the secretory function of b-cells, as Fas-deficient mice exhibited impaired glucose-induced insulin secretion (Schumann et al 2007). It would therefore appear that Pax4 is an integrated factor of the Fas/FLIP signal transduction pathway, which relays either the positive or negative effects of IL-1b pending levels of the cytokine.…”
Section: Pax4 As a Master Regulator Of Islet Developmentmentioning
confidence: 99%
“…Since DEDD Ϫ/Ϫ mice revealed glucose intolerance, it might be worthwhile to assess whether any dysfunction of DEDD is present, either in the whole body or in specific tissues, in a subset of type 2 diabetes patients. Schumann et al (39) reported that the Fas pathway, where many DED-containing elements are associated, is involved in ␤ cell secretory function. Thus, DED-containing proteins might also influence metabolic homeostasis through apoptosis cascades, although DEDD Ϫ/Ϫ cells or mice showed no apparent defect in apoptosis (10,11).…”
Section: Dedd Prevents Inhibitory Phosphorylation Of Mitotic S6k1mentioning
confidence: 99%